Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
By using sodium ion transition metal oxide containing iron nickel in the positive electrode active material of sodium ion batteries and forming an alkaline sodium compound coating layer, the problem of structural instability of layered transition metal oxides at high voltage is solved, and the structure of layered transition metal oxides is improved. The cycle stability and energy density of the battery are achieved.
Patent Information
- Application Number
- CN202310735567.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-20
AI Technical Summary
The existing layered transition metal oxides are unstable at high voltages, resulting in low cycling stability of sodium ion batteries.
Sodium ion transition metal oxide containing iron and/or nickel elements is used as the positive electrode active material, and an alkaline sodium compound coating layer is formed on its surface, so as to control the mass proportion of the coating layer to 0.1≤(b+c) In the range of /w≤0.5, to improve the structural stability of the material.
It significantly improves the cycling stability and energy density of the battery under high voltage, reduces the side reaction between sodium ion transition metal oxide and electrolyte, and extends the service life of the battery.
Smart Images

Figure CN119170756A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect.
[0003] Sodium ion battery is a kind of secondary battery, and layered transition metal oxide is a common positive electrode active material for sodium ion battery. Layered transition metal oxide can extract and deintercalate more sodium ions under high voltage, and has a higher specific capacity. However, the existing layered transition metal oxide is structurally unstable under high voltage, resulting in low cycle stability of the battery under high voltage.
[0004] Public Content
[0005] In view of the technical problems existing in the background technology, the present application provides a positive electrode active material, aiming to solve the problem of structural instability of the positive electrode active material under high voltage, thereby improving the cycle stability and energy density of the battery containing the positive electrode active material under high voltage.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, wherein the positive electrode active material comprises:
[0007] A core, the core comprising a sodium ion transition metal oxide containing iron and / or nickel, wherein the molar amount of the iron element is denoted as b, the molar amount of the nickel element is denoted as c, and 0≤b≤0.4, 0≤c≤0.4;
[0008] A coating layer is provided on at least a portion of the surface of the inner core, wherein the coating layer contains an alkaline sodium compound, wherein the mass proportion of the alkaline sodium compound is w% based on the total amount of the positive electrode active material, and satisfies: 0.1≤(b+c) / w≤0.5.
[0009] The positive electrode active material of the present application has a stable structure at high voltage, thereby improving the cycle stability and energy density of the battery containing the positive electrode active material at high voltage.
[0010] In some embodiments, 0.2≤(b+c) / w≤0.4. Thus, the structural stability of the positive electrode active material at high voltage can be improved, thereby improving the cycle stability and energy density of the battery containing the positive electrode active material at high voltage.
[0011] In some embodiments, the mass percentage w% of the alkaline sodium compound is 0.3 wt% - 5 wt%, optionally 0.5 wt% - 2 wt%. Thereby, the structural stability of the positive electrode active material at high voltages can be improved, thus improving the cycle stability and energy density of the battery containing the same at high voltages.
[0012] In some embodiments, the alkaline sodium compound includes at least one of sodium hydroxide and sodium carbonate, optionally sodium carbonate. Thereby, the structural stability of the positive electrode active material at high voltages can be improved, thus improving the cycle stability and energy density of the battery containing the same at high voltages.
[0013] In some embodiments, based on the total mass of the coating layer, the mass percentage of the sodium carbonate is higher than or equal to 80%. Thereby, the structural stability of the positive electrode active material at high voltages can be improved, thus improving the cycle stability and energy density of the battery containing the same at high voltages.
[0014] In some embodiments, based on the total mass of the coating layer, the mass percentage of the sodium hydroxide is lower than or equal to 10%. Thereby, the structural stability of the positive electrode active material at high voltages can be improved, thus improving the cycle stability and energy density of the battery containing the same at high voltages.
[0015] In some embodiments, the sodium ion transition metal oxide includes: Na x Mn a Fe b Ni c Q d O 2-e+δ F e , 0.5 ≤ x ≤ 1.2, 0 < a, 0 ≤ b ≤ 0.4, 0 ≤ c ≤ 0.4, 0 ≤ d, a + b + c + d = 1, 0 ≤ e ≤ 0.2, -0.1 ≤ δ ≤ 0.1, and Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W, and Bi.
[0016] In some embodiments, the sodium ion transition metal oxide includes: Na x Mn a Fe b Ni c Q d O 2-e+δ F e, 0.7 ≤ x ≤ 1.2, 0 < a, 0.1 ≤ b ≤ 0.4, 0.1 ≤ c ≤ 0.4, 0 ≤ d ≤ 0.3, a + b + c + d = 1, 0 ≤ e ≤ 0.2, -0.1 ≤ δ ≤ 0.1, Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W, and Bi, and optionally includes at least one of B, Mg, Al, Si, Ca, Ti, Co, Cu, Zn, Zr, Nb, Mo, La, and Bi. Based on the total amount of the positive electrode active material, the mass ratio of the alkaline sodium compound is 1 wt% - 2 wt%. Thereby, the structural stability of the positive electrode active material at high voltages can be improved, and thus the cycle stability and energy density of the battery containing the same at high voltages can be improved.
[0017] In some embodiments, at least one of the following conditions is satisfied: 0.3 ≤ a ≤ 0.6; 0.15 ≤ b ≤ 0.35; 0.15 ≤ c ≤ 0.35; 0.1 ≤ d ≤ 0.2.
[0018] In some embodiments, 0.5 ≤ (b + c) / a ≤ 2, and optionally 0.5 ≤ (b + c) / a ≤ 1.5. Thereby, the structural stability of the positive electrode active material at high voltages can be improved, and thus the cycle stability and energy density of the battery containing the same at high voltages can be improved.
[0019] In some embodiments, the phase of the sodium ion transition metal oxide includes the O3 phase, and the space group includes The layer spacing is 0.53 nm - 0.55 nm. Thereby, the capacity of the battery can be improved.
[0020] In some embodiments, the sodium ion transition metal oxide includes: Na x Mn a Ni c Q d O 2-e+δ F e, 0.5 ≤ x ≤ 1.2, 0 < a, 0.1 ≤ c ≤ 0.3, 0 ≤ d ≤ 0.3, a + c + d = 1, 0 ≤ e ≤ 0.2, -0.1 ≤ δ ≤ 0.1, Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W, and Bi, optionally at least one of B, Mg, Al, Si, Ca, Ti, Co, Cu, Zn, Zr, Nb, Mo, La, and Bi. Based on the total amount of the positive electrode active material, the mass ratio of the alkaline sodium compound is 0.5 wt% - 1.5 wt%. Thus, the structural stability of the positive electrode active material at high voltages can be improved, thereby enhancing the cycle stability and energy density of the battery containing it.
[0021] In some embodiments, at least one of the following conditions is satisfied: 0.5 ≤ a ≤ 0.8; 0.15 ≤ c ≤ 0.25; 0.05 ≤ d ≤ 0.15.
[0022] In some embodiments, 0.125 ≤ c / a ≤ 0.45, optionally 0.2 ≤ c / a ≤ 0.3. Thus, the structural stability of the positive electrode active material at high voltages can be improved, thereby enhancing the cycle stability and energy density of the battery containing it.
[0023] In some embodiments, the phase of the sodium ion transition metal oxide includes the P2 phase, the space group includes P63 / mmc, and the layer spacing is 0.55 nm - 0.57 nm. Thus, the rate performance and cycle stability of the battery can be improved.
[0024] In some embodiments, the BET specific surface area of the positive electrode active material is Sm 2 / g, and S and w satisfy the relationship: 0.3 ≤ w / S ≤ 3, optionally 0.5 ≤ w / S ≤ 2. Thus, the cycle stability of the battery can be improved.
[0025] In some embodiments, the positive electrode active material satisfies at least one of the following conditions: the D v 50 of the positive electrode active material is 2 μm - 20 μm, optionally 4 μm - 15 μm; the BET specific surface area of the positive electrode active material is 0.2 m 2 / g - 2 m 2 / g, optionally 0.3 m 2 / g - 2 m 2 / g; the tap density of the positive electrode active material under a pressure of 300 MPa is 3.1 g / cm 3 -3.8 g / cm 3 , optionally 3.2 g / cm 3 -3.6 g / cm 3.
[0026] Therefore, when the D of the positive electrode active material v 50. When at least one of the specific surface area and the compaction density under a pressure of 300 MPa is within the above range, the conduction distance of Na ions in the positive electrode active material is short and the surface side reactions are few, which promotes the positive electrode active material to exert its gram capacity and improves the capacity retention rate of the battery containing it.
[0027] The second aspect of the present application provides a method for preparing the positive electrode active material according to the first aspect, comprising:
[0028] A sodium ion transition metal oxide containing iron and / or nickel is provided, wherein the molar amount of the iron element is denoted as b, the molar amount of the nickel element is denoted as c, and 0≤b≤0.4, 0≤c≤0.4;
[0029] The sodium ion transition metal oxide and the alkaline sodium compound are mixed and sintered to obtain a positive electrode active material,
[0030] Wherein, based on the total amount of the positive electrode active material, the mass proportion of the alkaline sodium compound is w%, and 0.1≤(b+c) / w≤0.5.
[0031] Therefore, the present application can prepare the above-mentioned positive electrode active material with stable structure under high voltage, thereby improving the cycle stability and energy density of the battery containing the positive electrode active material under high voltage.
[0032] The third aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application or the positive electrode active material prepared by the method described in the second aspect.
[0033] The fourth aspect of the present application provides a battery, which includes the positive electrode plate described in the third aspect of the present application.
[0034] A fifth aspect of the present application provides an electrical device, which includes the battery described in the fourth aspect.
[0035] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the optional embodiments below. The accompanying drawings are only used for the purpose of illustrating the optional embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0037] Figure 1is a cross-sectional view of a positive electrode active material according to an embodiment of the present application;
[0038] Figure 2 is a schematic structural diagram of a battery according to one embodiment of the present application;
[0039] Figure 3 is a schematic structural diagram of a battery module according to an embodiment of the present application;
[0040] Figure 4 is a schematic structural diagram of a battery pack according to an embodiment of the present application;
[0041] Figure 5 yes Figure 4 Exploded diagram of
[0042] Figure 6 is a schematic diagram of an embodiment of an electrical device in which a battery is used as a power source;
[0043] Figure 7 This is a surface morphology of the positive electrode active material prepared in Example 1;
[0044] Figure 8 This is a surface morphology of the positive electrode active material prepared in Comparative Example 1;
[0045] Fig. 9 This is a surface morphology of the positive electrode active material of the button battery of Example 1 after being disassembled after 50 cycles;
[0046] Fig.10 This is a surface morphology of the positive electrode active material of the button battery of Comparative Example 1 after being disassembled after 50 cycles.
[0047] Description of reference numerals:
[0048] 1000: positive electrode active material; 100: core; 200: coating layer; 1: secondary battery; 2: battery module; 3: battery pack; 4: upper case; 5: lower case. DETAILED DESCRIPTION
[0049] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0050] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0051] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0052] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0054] Secondary batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but are also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. Compared with traditional lithium-ion batteries, sodium-ion batteries have a strong price advantage and have broad application prospects in large-scale power storage systems.
[0055] Layered transition metal oxides have become one of the popular positive electrode active materials for sodium ion batteries due to their high electrical conductivity, high energy density, large capacity and long cycle life. Under high-voltage charging conditions, more sodium ions are released from the layered transition metal oxides, giving them a higher specific capacity. However, the high activity of oxygen in the layered transition metal oxides is high, and the highly active oxygen easily reacts with the metal in the transition metal oxides to cause the metal to migrate to the electrolyte. The highly active oxygen also easily reacts with the electrolyte, resulting in metal dissolution and oxygen deficiency in the transition metal oxides, causing cracks in the layered transition metal oxides, reducing the structural stability of the layered transition metal oxides, and thus making the battery have low cycle stability at high voltages.
[0056] In the present application, the positive electrode active material includes a core and a coating layer provided on at least a portion of the surface of the core, the core includes a sodium ion transition metal oxide containing iron and / or nickel elements, wherein the molar amount of the iron element is denoted as b, the molar amount of the nickel element is denoted as c, 0≤b≤0.4, 0≤c≤0.4, due to the high activity of nickel and iron in the sodium ion transition metal oxide, it is easy to induce an increase in the oxygen activity of adjacent oxygen sites, thus the present application controls the molar amount of the iron element b and the molar amount of the nickel element c to be within the above range, which can reduce the content of highly active oxygen in the transition metal oxide. At the same time, the coating layer contains an alkaline sodium compound, and based on the total amount of the positive electrode active material, the mass proportion of the alkaline sodium compound is w%, and the iron element and / or nickel element in the sodium ion transition metal oxide in the kernel of the present application and the alkaline sodium compound in the coating layer satisfy: 0.1≤(b+c) / w≤0.5. The kernel and coating layer satisfying this composition can reduce the surface activity of the sodium ion transition metal oxide while increasing the specific capacity of the positive electrode active material, and the coating layer can also effectively isolate the sodium ion transition metal oxide from contact with the electrolyte, reduce the side reaction between the electrolyte and the surface of the transition metal oxide, reduce metal dissolution and oxygen deficiency, and improve the structural stability of the positive electrode active material under high voltage, thereby improving the cycle stability and energy density of the battery containing it under high voltage.
[0057] The positive electrode active material disclosed in the embodiment of the present application is suitable for secondary batteries, and the battery disclosed in the embodiment of the present application can be used in electrical equipment using the battery as a power source or various energy storage systems using the battery as an energy storage element. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.
[0058] The first aspect of the present application proposes a positive electrode active material, referring to Figure 1 The positive electrode active material 1000 includes a core 100 and a coating layer 200, wherein the core 100 includes a sodium ion transition metal oxide containing iron and / or nickel elements, wherein the molar amount of the iron element is denoted as b, and the molar amount of the nickel element is denoted as c, 0≤b≤0.4, 0≤c≤0.4; the coating layer 200 is disposed on at least a portion of the surface of the core 100, and the coating layer 200 contains an alkaline sodium compound, and based on the total amount of the positive electrode active material 1000, the mass proportion of the alkaline sodium compound is w%, and satisfies: 0.1≤(b+c) / w≤0.5.
[0059] The positive electrode active material 1000 of the present application includes a core 100 and a coating layer 200 provided on at least a portion of the surface of the core 100, wherein the core 100 includes a sodium ion transition metal oxide containing iron and / or nickel elements, wherein the molar amount of the iron element is denoted as b, and the molar amount of the nickel element is denoted as c, 0≤b≤0.4, 0≤c≤0.4. Since nickel and iron in the sodium ion transition metal oxide are highly active, they can easily induce an increase in the oxygen activity of adjacent oxygen sites. Therefore, the present application controls the molar amount b of the iron element and the molar amount c of the nickel element to be within the above range, thereby reducing the content of highly active oxygen in the transition metal oxide. At the same time, the coating layer 200 contains an alkaline sodium compound, and based on the total amount of the positive electrode active material, the mass proportion of the alkaline sodium compound is w%, and the iron element and / or nickel element in the sodium ion transition metal oxide in the core 100 of the present application and the alkaline sodium compound in the coating layer 200 satisfy: 0.1≤(b+c) / w≤0.5. The core 100 and the coating layer 200 satisfying this composition can reduce the surface activity of the sodium ion transition metal oxide while increasing the specific capacity of the positive electrode active material 1000, and the coating layer 200 can also effectively isolate the sodium ion transition metal oxide from contact with the electrolyte, reduce the side reaction between the electrolyte and the surface of the sodium ion transition metal oxide, reduce metal dissolution and oxygen deficiency, and improve the structural stability of the positive electrode active material 1000 under high voltage, thereby improving the cycle stability and energy density of the battery containing it under high voltage.
[0060] In some embodiments of the present application, the core 100 includes a sodium ion transition metal oxide containing iron and / or nickel, in which the molar amount of the iron element is denoted as b, the molar amount of the nickel element is denoted as c, 0≤b≤0.4, 0≤c≤0.4, for example, 0.001≤b≤0.4, 0.005≤b≤0.4, 0.01≤b≤0.4, 0.015≤b≤0.4, 0.02≤b≤0.4, 0.05≤b≤0.4, 0.07≤b≤0.4, 0.1≤b≤0.4, 0.12≤b≤0.4, 0.15≤b≤0.4, 0.17≤b≤0.4, 0.2≤b≤0.4, 0.22≤b≤0.4, 0.25≤b≤0.4, 0.27≤b ≤0.4, 0.3≤b≤0.4, 0.32≤b≤0.4, 0.35≤b≤0.4, 0.37≤b≤0.4, etc.; 0.001≤c≤0.4, 0.005≤c≤0.4, 0.01≤c≤0.4, 0.015≤c≤0.4, 0.02≤c≤0.4, 0.05≤c≤0.4, 0.07≤c≤0.4, 0.1≤c≤0.4, 0.12≤c≤0.4, 0.15≤c≤0.4, 0.17≤c≤0.4, 0.2≤c≤0.4, 0.22≤c≤0.4, 0.25≤c≤0.4, 0.27≤c≤0.4, 0.3≤c≤0.4, 0.32≤c≤0.4, 0.35≤c≤0.4, 0.37≤c≤0.4, etc. Specifically, since the nickel and iron in the sodium ion transition metal oxide are highly active, they can easily induce the increase of the oxygen activity of the adjacent oxygen sites. Therefore, the present application controls the molar amount b of the iron element and the molar amount c of the nickel element to be within the above range, which can reduce the content of highly active oxygen in the transition metal oxide, thereby reducing the metal dissolution and oxygen deficiency in the transition metal oxide, and improving the structural stability of the positive electrode active material 1000 under high voltage.
[0061] In some embodiments of the present application, based on the total amount of the positive electrode active material 1000, the mass proportion of the alkaline sodium compound is w%, and satisfies: 0.1≤(b+c) / w≤0.5, for example, 0.15≤(b+c) / w≤0.45, 0.2≤(b+c) / w≤0.4, 0.25≤(b+c) / w≤0.35, 0.25≤(b+c) / w≤0.3, etc. In other embodiments of the present application, the mass proportion of the alkaline sodium compound is w%, and satisfies 0.2≤(b+c) / w≤0.4. Therefore, the core 100 and the coating layer 200 that meet this composition can reduce the surface activity of the sodium ion transition metal oxide while increasing the specific capacity of the positive electrode active material 1000, and the coating layer 200 can also effectively isolate the sodium ion transition metal oxide from contact with the electrolyte, reduce the side reaction between the electrolyte and the surface of the sodium ion transition metal oxide, reduce metal dissolution and oxygen deficiency, and improve the structural stability of the positive electrode active material 1000 under high voltage, thereby improving the cycle stability and energy density of the battery containing it under high voltage.
[0062] In some embodiments of the present application, the mass percentage w% of the alkaline sodium compound is 0.3wt%-5wt%, such as 0.5wt%-4.5wt%, 0.8wt%-4.2wt%, 1wt%-4wt%, 1.2wt%-3.7wt%, 1.5wt%-3.5wt%, 1.8wt%-3.2wt%, 2wt%-3wt%, 2.2wt%-2.8wt%, 2.5wt%-2.7wt%, etc. In other embodiments of the present application, the mass percentage w% of the alkaline sodium compound is 0.5wt%-2wt%. Thus, the mass percentage of the alkaline sodium compound in the coating layer 200 of the positive electrode active material 1000 of the present application meets the above range, which can effectively isolate the sodium ion transition metal oxide from contacting with the electrolyte, reduce the side reaction between the electrolyte and the surface of the sodium ion transition metal oxide, reduce metal dissolution and oxygen deficiency, and improve the structural stability of the positive electrode active material 1000 under high voltage, thereby improving the cycle stability and energy density of the battery containing it under high voltage.
[0063] In some embodiments of the present application, the alkaline sodium compound includes at least one of sodium hydroxide and sodium carbonate. In other embodiments of the present application, the alkaline sodium compound includes sodium carbonate. Thus, the coating layer 200 composed of the above-mentioned alkaline sodium compound can effectively isolate the sodium ion transition metal oxide from contacting the electrolyte, reduce the side reaction between the electrolyte and the surface of the sodium ion transition metal oxide, reduce metal dissolution and oxygen deficiency, and improve the structural stability of the positive electrode active material 1000 under high voltage, thereby improving the cycle stability and energy density of the battery containing it under high voltage.
[0064] In some embodiments of the present application, based on the total mass of the coating layer 200, the mass proportion of sodium carbonate is higher than or equal to 80%, such as 80%-100%, 82%-98%, 85%-95%, 87%-92%, 90%-92%, etc. Thus, the coating layer 200 contains sodium carbonate in the above content, and the sodium carbonate is more evenly distributed on the surface of the inner core 100, and the formed coating layer 200 is more uniform, which can effectively isolate the sodium ion transition metal oxide from contacting with the electrolyte, reduce the side reaction between the electrolyte and the surface of the sodium ion transition metal oxide, reduce metal dissolution and oxygen deficiency, improve the structural stability of the positive electrode active material 1000 at high voltage, and thus improve the cycle stability and energy density of the battery containing it at high voltage.
[0065] In some embodiments of the present application, based on the total mass of the coating layer 200, the mass proportion of sodium hydroxide is lower than or equal to 10%, such as 9%-10%, 8%-8.5%, 7%-7.8%, 6%-6.8%, 5%-5.8%, 4%-4.8%, 3%-3.8%, 2%-2.8%, 1%-1.8%, 0%-1%, etc. Specifically, the sodium hydroxide in the coating layer 200 is likely to have a side reaction with the binder in the positive electrode slurry, resulting in serious gelation of the slurry. And sodium hydroxide is likely to generate water molecules during the formation of the coating layer 200, and the water molecules react with the lithium salt sodium hexafluorophosphate in the battery electrolyte and are easily converted into HF, thereby reducing the cycle stability of the battery. Thus, the mass proportion of sodium hydroxide in the coating layer 200 of the present application within the above range can reduce the gelation of the positive electrode slurry while improving the cycle stability of the battery containing it at high voltage.
[0066] In some embodiments of the present application, the sodium ion transition metal oxide in the above inner core 100 includes:
[0067] Na x Mn a Fe b Ni c Q d O 2-e+δ F e ,
[0068] 0.5≤x≤1.2, 0 < a, 0≤b≤0.4, 0≤c≤0.4, 0≤d, a + b + c + d = 1, 0≤e≤0.2, -0.1≤δ≤0.1, and Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W, and Bi.
[0069] In some specific embodiments of the present application, the sodium ion transition metal oxide in the above-mentioned core 100 includes:
[0070] Na x Mn a Fe b Ni c Q d O 2-e+δ F e ,
[0071] 0.7 ≤ x ≤ 1.2, 0 < a, 0.1 ≤ b ≤ 0.4, 0.1 ≤ c ≤ 0.4, 0 ≤ d ≤ 0.3, a + b + c + d = 1, 0 ≤ e ≤ 0.2, -0.1 ≤ δ ≤ 0.1, Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W, and Bi, optionally at least one of B, Mg, Al, Si, Ca, Ti, Co, Cu, Zn, Zr, Nb, Mo, La, and Bi. Based on the total amount of the positive electrode active material 1000, the mass ratio of the alkaline sodium compound is 1 wt% - 2 wt%, such as 1.2 wt% - 2 wt%, 1.5 wt% - 2 wt%, 1.8 wt% - 2 wt%, etc. Thus, the mass ratio of the alkaline sodium compound in the coating layer 200 on the surface of the sodium ion transition metal oxide core 100 composed of the present application satisfies the above range, which can effectively isolate the sodium ion transition metal oxide from contacting with the electrolyte, reduce the side reaction between the electrolyte and the surface of the sodium ion transition metal oxide, reduce metal dissolution and oxygen deficiency, improve the structural stability of the positive electrode active material 1000 at high voltages, and thus improve the cycle stability and energy density of the battery containing it at high voltages.
[0072] In some embodiments of the present application, in the above-mentioned sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e x can take 0.7 ≤ x ≤ 1.2, such as 0.7 ≤ x ≤ 1.1, 0.8 ≤ x ≤ 1, 0.85 ≤ x ≤ 1, 0.88 ≤ x ≤ 1, 0.9 ≤ x ≤ 1, 0.95 ≤ x ≤ 1, 0.98 ≤ x ≤ 1, etc. Thus, the inclusion of this content of sodium element in the sodium ion transition metal oxide enables the battery to have a relatively high capacity.
[0073] It should be noted that in the positive electrode, battery or electrical equipment, as the battery undergoes formation and circulation processes, sodium ions will be consumed, so the measured sodium content x in the sodium ion transition metal oxide will be less than 1. At the same time, if the positive electrode and the negative electrode use a sodium supplement, the measured sodium content x in the sodium ion transition metal oxide will be greater than 1 after the battery undergoes formation and circulation processes.
[0074] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Where a can be a>0, for example, 0.001≤a<1, 0.005≤a≤0.9, 0.1≤a≤0.8, 0.2≤a≤0.7, 0.3≤a≤0.6, 0.4≤a≤0.5, etc. Thus, the sodium ion transition metal oxide includes this content of manganese, which can effectively improve the structural stability of the sodium ion transition metal oxide and improve the cycle stability of the battery containing it. In other embodiments of the present application, the above-mentioned sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Here a can be 0.3≤a≤0.6.
[0075] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Where b can be 0.1≤b≤0.4, for example, 0.1≤b≤0.35, 0.15≤b≤0.3, 0.2≤b≤0.25, 0.22≤b≤0.25, etc. Thus, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Including this content of Fe can not only reduce the high active oxygen content in the sodium ion transition metal oxide, but also increase the specific capacity of the positive electrode active material 1000. In other embodiments of the present application, the above-mentioned sodium ion transition metal oxide Na x Mna Fe b Ni c Q d O 2-e+δ F e Here b can be 0.15≤b≤0.35.
[0076] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Where c is 0.1≤c≤0.40, for example, 0.1≤c≤0.35, 0.15≤c≤0.3, 0.2≤c≤0.25, 0.22≤c≤0.25, etc. Thus, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Including this content of Ni can not only reduce the high active oxygen content in the sodium ion transition metal oxide, but also increase the specific capacity of the positive electrode active material 1000. In other embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Here c is taken as 0.15≤c≤0.35.
[0077] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Wherein Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W and Bi. In other embodiments of the present application, the above-mentioned sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F eThe Q includes at least one of B, Mg, Al, Si, Ca, Ti, Co, Cu, Zn, Zr, Nb, Mo, La and Bi.
[0078] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Where d is 0≤d≤0.3, for example, 0.001≤d≤0.3, 0.005≤d≤0.3, 0.01≤d≤0.3, 0.05≤d≤0.3, 0.1≤d≤0.3, 0.15≤d≤0.3, 0.17≤d≤0.27, 0.2≤d≤0.25, 0.2≤d≤0.22, etc. Thus, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Including the Q element in this content can improve the structural stability of the positive electrode active material 1000. In other embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Here d is taken as 0.1≤d≤0.2.
[0079] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Here, δ is -0.1≤δ≤0.1, and e is 0≤e≤0.2, for example, -0.09≤δ≤0.09, -0.08≤δ≤0.08, -0.07≤δ≤0.07, -0.06≤δ≤0.06, -0.05≤δ≤0.05, -0.04≤δ≤0.04, -0.03≤δ≤0.03, -0.02≤δ≤0.02, -0.01≤δ≤0.01, -0.01≤δ≤0, 0≤δ≤0.01, etc., 0.01≤e≤0.2, 0.02≤e≤0.18, 0.05≤e≤0.15, 0.08≤e≤0.12, 0.1≤e≤0.12, etc.
[0080] Specifically, the sodium ion transition metal oxide Na of the present application x Mn a Fe b Ni c Q d O 2-e+δ F e Doping F with this content in the middle oxygen position can effectively stabilize the oxygen in the sodium ion transition metal oxide, thereby reducing the structural damage caused by lattice oxygen release in the sodium ion transition metal oxide, improving the stability of the positive electrode active material 1000, and further improving the cycle stability of the battery.
[0081] It should be noted that in the positive electrode, battery or electrical equipment, since the battery undergoes cycles and other processes, the oxygen element in the sodium ion transition metal oxide is lost, so the measured oxygen element content 2+δ-e in the sodium ion transition metal oxide may be less than 2.
[0082] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e 0.5≤(b+c) / a≤2, for example, 0.8≤(b+c) / a≤2, 1≤(b+c) / a≤1.8, 1.2≤(b+c) / a≤1.6, 1.5≤(b+c) / a≤1.6, etc. In other embodiments of the present application, the above-mentioned sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e 0.5≤(b+c) / a≤1.5. Specifically, Ni can contribute to capacity, but the change of Fe and Ni valence easily leads to structural instability, while Mn can stabilize the structure of the sodium ion transition metal oxide. Therefore, the molar amount a of Mn, the molar amount b of Fe and the molar amount c of Ni in the sodium ion transition metal oxide of the present application satisfy the above relationship, which can improve the specific capacity of the sodium ion transition metal oxide while improving its structural stability at high voltage, thereby improving the cycle stability and energy density of the battery containing it at high voltage.
[0083] In some embodiments of the present application, the above-mentioned sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O2-e+δ F e The phases include O3 phase, and the space groups include The interlayer spacing is 0.53nm-0.55nm, for example, the interlayer spacing may be 0.532nm-0.55nm, 0.535nm-0.548nm, 0.537nm-0.545nm, 0.540nm-0.542nm, etc. Specifically, the formed O3 phase sodium ion transition metal oxide has a high Na content, so that the battery capacity is high.
[0084] It should be noted that the sodium ion transition metal oxide Na in this application x Mn a Fe b Ni c Q d O 2-e+δ F e The phase state, space group and interlayer spacing can be characterized by X-ray diffraction.
[0085] Specifically, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e The interlayer spacing d of the 003 crystal plane 003 The space group test method includes: grinding the sample to be tested in an agate mortar in a dry room or glove box and then passing it through a 350-mesh sieve, taking an appropriate amount of the sieved sample and placing it in the middle of the groove of the sample rack so that the loose sample powder is slightly higher than the plane of the sample rack; taking a glass slide and gently pressing the sample surface to make the sample surface consistent with the frame plane after scraping it flat, and scraping off the excess powder. After the sample is prepared, a Brucker D8A_A25 X-ray powder diffractometer from Brucker AxS of Germany was used to measure the CuK α The ray is the radiation source, and the wavelength of the ray is The scanning 2θ angle range is 5°-60°, and the scanning rate is 4° / min. After the test is completed, the angle corresponding to the 003 crystal plane is used. According to the Bragg equation 2d·sinθ=λ, and each unit cell of the 003 crystal plane contains three transition metal layers, the interlayer spacing d of the 003 crystal plane can be obtained. 003 By comparing the XRD diffraction peaks of the sample with the standard card of the XRD analysis software, the space group and crystal phase of the sample can be confirmed.
[0086] In some further specific embodiments of the present application, the sodium ion transition metal oxide in the core 100 comprises:
[0087] Na x Mn aNi c Q d O 2-e+δ F e ,
[0088] 0.5 ≤ x ≤ 1.2, 0 < a, 0.1 ≤ c ≤ 0.3, 0 ≤ d ≤ 0.3, a + c + d = 1, 0 ≤ e ≤ 0.2, -0.1 ≤ δ ≤ 0.1, Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W, and Bi, and optionally at least one of B, Mg, Al, Si, Ca, Ti, Co, Cu, Zn, Zr, Nb, Mo, La, and Bi. Based on the total amount of the positive electrode active material 1000, the mass ratio of the basic sodium compound is 0.5 wt% - 1.5 wt%, such as 0.5 wt% - 1.3 wt%, 0.7 wt% - 1 wt%, 0.9 wt% - 1 wt%, etc. Thus, the mass ratio of the basic sodium compound in the coating layer 200 on the surface of the sodium ion transition metal oxide core 100 composed in this application satisfies the above range, which can effectively isolate the sodium ion transition metal oxide from contacting the electrolyte, reduce the side reaction between the electrolyte and the surface of the sodium ion transition metal oxide, reduce metal dissolution and oxygen deficiency, improve the structural stability of the positive electrode active material 1000, and thereby improve the cycle stability and energy density of the battery containing it at high voltages.
[0089] In some embodiments of this application, the above sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e in which x can take 0.5 ≤ x ≤ 1.2, such as 0.5 ≤ x ≤ 1.1, 0.6 ≤ x ≤ 1.1, 0.8 ≤ x ≤ 1, 0.85 ≤ x ≤ 1, 0.88 ≤ x ≤ 1, 0.9 ≤ x ≤ 1, 0.95 ≤ x ≤ 1, 0.98 ≤ x ≤ 1, etc. Thus, the sodium ion transition metal oxide includes this content of sodium element, making the battery have a higher capacity.
[0090] It should be noted that in the positive electrode plate, battery, or electrical device, due to processes such as formation and cycling of the battery, sodium ions will be consumed, so there will be a situation where the measured sodium element content x in the sodium ion transition metal oxide is less than 1. At the same time, if a sodium supplement agent is used for the positive electrode plate and the negative electrode plate, after processes such as formation and cycling of the battery, there will be a situation where the measured sodium element content x in the sodium ion transition metal oxide is greater than 1.
[0091] In some embodiments of this application, the above sodium ion transition metal oxide Nax Mn a Ni c Q d O 2-e+δ F e Where a can be a>0, for example, 0.001≤a<1, 0.005≤a≤0.9, 0.1≤a≤0.8, 0.2≤a≤0.7, 0.3≤a≤0.6, 0.4≤a≤0.5, etc. Thus, the sodium ion transition metal oxide includes this content of manganese, which can effectively improve the structural stability of the sodium ion transition metal oxide and improve the cycle stability of the battery containing it. In other embodiments of the present application, the above-mentioned sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e Here a can be 0.5≤a≤0.8.
[0092] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e Where c is 0.1≤c≤0.3, for example, 0.15≤c≤0.3, 0.2≤c≤0.25, 0.22≤c≤0.25, etc. Thus, the sodium ion transition metal oxide Na x Mn a Fe b Ni c Q d O 2-e+δ F e Including this content of Ni can not only reduce the high active oxygen content in the sodium ion transition metal oxide, but also increase the specific capacity of the positive electrode active material 1000. In other embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e Here c is taken as 0.15≤c≤0.25.
[0093] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F eWherein Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W and Bi. In other embodiments of the present application, the above-mentioned sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e The Q includes at least one of B, Mg, Al, Si, Ca, Ti, Co, Cu, Zn, Zr, Nb, Mo, La and Bi.
[0094] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e Where d is 0≤d≤0.3, for example, 0.001≤d≤0.3, 0.005≤d≤0.3, 0.01≤d≤0.3, 0.05≤d≤0.3, 0.1≤d≤0.3, 0.15≤d≤0.3, 0.17≤d≤0.27, 0.2≤d≤0.25, 0.2≤d≤0.22, etc. Thus, the sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e Including the Q element in this content can improve the structural stability of the positive electrode active material 1000. In other embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e Here d is taken as 0.05≤d≤0.15.
[0095] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F eHere, δ is -0.1≤δ≤0.1, and e is 0≤e≤0.2, for example, -0.09≤δ≤0.09, -0.08≤δ≤0.08, -0.07≤δ≤0.07, -0.06≤δ≤0.06, -0.05≤δ≤0.05, -0.04≤δ≤0.04, -0.03≤δ≤0.03, -0.02≤δ≤0.02, -0.01≤δ≤0.01, -0.01≤δ≤0, 0≤δ≤0.01, etc., 0.01≤e≤0.2, 0.02≤e≤0.18, 0.05≤e≤0.15, 0.08≤e≤0.12, 0.1≤e≤0.12, etc.
[0096] Specifically, the sodium ion transition metal oxide Na of the present application x Mn a Ni c Q d O 2-e+δ F e Doping F with this content in the middle oxygen position can effectively stabilize the oxygen in the sodium ion transition metal oxide, thereby reducing the structural damage caused by lattice oxygen release in the sodium ion transition metal oxide, improving the stability of the positive electrode active material 1000, and further improving the cycle stability of the battery.
[0097] It should be noted that in the positive electrode, battery or electrical equipment, since the battery undergoes cycles and other processes, the oxygen element in the sodium ion transition metal oxide is lost, so the measured oxygen element content 2+δ-e in the sodium ion transition metal oxide may be less than 2.
[0098] In some embodiments of the present application, the sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e 0.125≤c / a≤0.45, for example, 0.15≤c / a≤0.45, 0.175≤c / a≤0.425, 0.2≤c / a≤0.4, 0.225≤c / a≤0.375, 0.25≤c / a≤0.35, 0.275≤c / a≤0.325, 0.3≤c / a≤0.325, etc. In other embodiments of the present application, the above-mentioned sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e0.2≤c / a≤0.3. Specifically, Ni can contribute to capacity, but Ni changes valence and easily leads to structural instability, while Mn can stabilize the structure of the sodium ion transition metal oxide. Therefore, the molar amount a of Mn and the molar amount c of Ni in the sodium ion transition metal oxide of the present application satisfy the above relationship, which can improve the specific capacity of the sodium ion transition metal oxide while improving its structural stability at high voltage, thereby improving the cycle stability and energy density of the battery containing it at high voltage.
[0099] In some embodiments of the present application, the above-mentioned sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e The phase includes a P2 phase, a space group includes P63 / mmc, and an interlayer spacing of 0.55nm-0.57nm, for example, the interlayer spacing can be 0.552nm-0.57nm, 0.555nm-0.568nm, 0.557nm-0.565nm, 0.56nm-0.562nm, etc. Specifically, the interlayer spacing of the formed P2 phase sodium ion transition metal oxide is large, which can improve the transmission rate of Na ions and maintain the integrity of the layered structure, so that the battery has excellent rate performance and cycle performance.
[0100] It should be noted that the sodium ion transition metal oxide Na in this application x Mn a Ni c Q d O 2-e+δ F e The phase state, space group and interlayer spacing can be characterized by X-ray diffraction.
[0101] Specifically, the sodium ion transition metal oxide Na x Mn a Ni c Q d O 2-e+δ F e The interlayer spacing d of the 003 crystal plane 003 The space group test method includes: grinding the sample to be tested in an agate mortar in a dry room or glove box and then passing it through a 350-mesh sieve, taking an appropriate amount of the sieved sample and placing it in the middle of the groove of the sample rack so that the loose sample powder is slightly higher than the plane of the sample rack; taking a glass slide and gently pressing the sample surface to make the sample surface consistent with the frame plane after scraping it flat, and scraping off the excess powder. After the sample is prepared, a Brucker D8A_A25 X-ray powder diffractometer from Brucker AxS of Germany was used to measure the CuK α The ray is the radiation source, and the wavelength of the ray is The scanning 2θ angle range is 5°-60°, and the scanning rate is 4° / min. After the test is completed, the angle corresponding to the 003 crystal plane is used. According to the Bragg equation 2d·sinθ=λ, and each unit cell of the 003 crystal plane contains three transition metal layers, the interlayer spacing d of the 003 crystal plane can be obtained. 003 By comparing the XRD diffraction peaks of the sample with the standard card of the XRD analysis software, the space group and crystal phase of the sample can be confirmed.
[0102] In some embodiments of the present application, the BET specific surface area of the positive electrode active material 1000 is Sm 2 / g, S and w satisfy the relationship: 0.3≤w / S≤3, for example, 0.5≤w / S≤2.8, 0.7≤w / S≤2.5, 1≤w / S≤2.2, 1.3≤w / S≤2, 1.5≤w / S≤1.8, etc. In other embodiments of the present application, S and w in the positive electrode active material 1000 satisfy the relationship: 0.5≤w / S≤2. Therefore, S and W in the positive electrode active material 1000 of the present application satisfy the above relationship, which can effectively isolate the sodium ion transition metal oxide from contact with the electrolyte while improving the specific capacity of the positive electrode activity, reduce the side reaction between the electrolyte and the surface of the transition metal oxide, reduce metal dissolution and oxygen deficiency, and improve the structural stability of the positive electrode active material 1000, thereby improving the cycle stability and energy density of the battery containing it at high voltage.
[0103] In some embodiments of the present application, the D of the positive electrode active material 1000 v 50 is 2 μm-20 μm, for example, D v 50 can be 2 μm-19 μm, 4 μm-18 μm, 5 μm-15 μm, 6 μm-14 μm, 8 μm-13 μm, 9 μm-12 μm, 10 μm-11 μm, etc. In other embodiments of the present application, the D v 50 is 4μm-15μm.
[0104] In this application, D v 50 refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%, for example, with reference to the standard GB / T 19077-2016, and measured using a laser particle size analyzer (such as Malvern Master Size 3000).
[0105] In some embodiments of the present application, the BET specific surface area of the positive electrode active material 1000 is 0.2 m 2 / g-2m 2 / g, for example, the specific surface area of the positive electrode active material can be 0.2m 2 / g-1.5m2 / g,0.2m 2 / g-1m 2 / g,0.3m 2 / g-0.8m 2 / g,0.3m 2 / g-0.5m 2 In some other embodiments of the present application, the specific surface area of the positive electrode active material 1000 is 0.3 m 2 / g-2m 2 / g.
[0106] In the present application, the BET specific surface area of the positive electrode active material 1000 has a well-known meaning in the art and can be measured using instruments and methods well-known in the art. For example, it can be tested by referring to the following method: using the American Micromeritics multi-station fully automatic specific surface area and pore analyzer GeminiVII2390, take about 7g of the sample and put it into a 9cc long tube with a bulb, degas at 200°C for 2h, and then put it into the host for testing to obtain the BET specific surface area data of the positive electrode active material 1000.
[0107] In some embodiments of the present application, the compaction density of the positive electrode active material 1000 at a pressure of 300 MPa is 3.1 g / cm 3 -3.8g / cm 3 For example, the compaction density of the positive electrode active material 1000 at a pressure of 300 MPa may be 3.0 g / cm 3 -3.8g / cm 3 , 3.2g / cm 3 -3.5g / cm 3 , 3.2g / cm 3 -3.4g / cm 3 In some embodiments of the present application, the compaction density of the positive electrode active material 1000 under a pressure of 300 MPa is 3.2 g / cm 3 -3.6g / cm 3 .
[0108] In the present application, "compacted density" has a well-known meaning in the art and can be measured by instruments and methods well-known in the art. For example, the following test method can be used: a certain amount of powder m is placed in a special compaction mold, the mold is placed on a compaction density instrument, a pressure of 300 MPa is set, and the thickness and volume v of the powder under a pressure of 300 MPa is measured on the equipment. The compacted density is calculated by density = mass m / volume v; (for details, refer to GB / T24533-2009).
[0109] Specifically, when the positive electrode active material D of the present application is 1000 v50. When at least one of the specific surface area and the compaction density under a pressure of 300 MPa is within the above range, the conduction distance within the positive electrode active material 1000 is small and the surface side reactions are small, which promotes the positive electrode active material to exert its gram capacity and improves the capacity retention rate of the battery containing it.
[0110] In the present application, the elemental composition of the positive electrode active material 1000 can be determined by instruments and methods known in the art, such as inductively coupled plasma emission spectrometry: the instrument standard refers to EPA6010D-2014 "Inductively Coupled Plasma Atomic Emission Spectrometry". The sample is treated by chemical methods to be digested into a solution, atomized into plasma and excited to produce characteristic spectral lines of the elements, and the element content is qualitatively and quantitatively analyzed according to the wavelength and intensity of the spectral lines (proportional to the concentration).
[0111] The alkaline sodium compound Na in the coating layer 200 of the positive electrode active material 1000 2 CO 3 The content test can be measured by using instruments and methods known in the art, for example, by referring to GB / T 9736-2008 standard. Under an atmosphere free of carbon dioxide, 30 g of the obtained positive electrode active material powder is weighed, 100 ml of pure water is added and stirred for 30 min, and after standing for 10 min, a certain amount of filtrate is removed and titrated with 0.05 mol / L hydrochloric acid standard solution. The instrument used is a Mettler T5 titrator.
[0112] The content of the basic sodium compound NaOH in the coating layer 200 of the positive electrode active material 1000 can be measured by using instruments and methods known in the art, for example, by referring to the GB / T 9736-2008 standard. Under an atmosphere free of carbon dioxide and dehumidification, 30 g of the obtained layered oxide powder is weighed, 100 ml of anhydrous ethanol is added and stirred for 30 min, and 10 ml of the filtrate is removed after standing for 10 min and filtered, and then diluted with 50 ml of ultrapure water, and then titrated with a 0.05 mol / L hydrochloric acid standard solution, and the instrument used is a Mettler T5 titrator.
[0113] The sodium content of the sodium ion transition metal oxide in the core 100 of the present invention can be obtained by subtracting the sodium content of the alkaline sodium compounds NaOH and NaOH in the coating layer obtained by the above-mentioned inductively coupled plasma emission spectrometry method from the total amount of sodium. 2 CO 3 The content of other elements in the composition of the sodium ion transition metal oxide can be obtained by the above-mentioned inductively coupled plasma emission spectrometry test, thereby obtaining the composition of the sodium ion transition metal oxide. The mass proportion of the alkaline sodium compound in the above-mentioned positive electrode active material 1000 can be calculated by the alkaline sodium compounds NaOH and Na 2 CO3 is obtained by adding up the contents.
[0114] The second aspect of the present application provides a method for preparing the cathode active material described in the first aspect, including:
[0115] S100: Provide a sodium-ion transition metal oxide containing iron element and / or nickel element
[0116] In some embodiments of the present application, in the sodium-ion transition metal oxide, the molar amount of iron element is denoted as b, and the molar amount of nickel element is denoted as c, where 0 ≤ b ≤ 0.4 and 0 ≤ c ≤ 0.4.
[0117] In the present application, the sodium-ion transition metal oxide may include: Na x Mn a Fe b Ni c Q d O 2-e+δ F e , for example, the sodium-ion transition metal oxide includes the above-mentioned Na x Mn a Fe b Ni c Q d O 2-e+δ F e , 0.7 ≤ x ≤ 1.2, 0 < a, 0.1 ≤ b ≤ 0.4, 0.1 ≤ c ≤ 0.4, 0 ≤ d ≤ 0.3, a + b + c + d = 1, 0 ≤ e ≤ 0.2, -0.1 ≤ δ ≤ 0.1, and Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W, and Bi; or for another example, the sodium-ion transition metal oxide includes the above-mentioned Na x Mn a Ni c Q d O 2-e+δ F e , 0.5 ≤ x ≤ 1.2, 0 < a, 0.1 ≤ c ≤ 0.3, 0 ≤ d ≤ 0.3, a + c + d = 1, 0 ≤ e ≤ 0.2, -0.1 ≤ δ ≤ 0.1, and Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W, and Bi.
[0118] In some embodiments of the present application, the preparation method of the above-mentioned sodium ion transition metal oxide may include: mixing the Na source, Fe source, Mn source, Ni source and Q source according to the composition of the above-mentioned sodium ion transition metal oxide, pre-grinding them in an agate mortar, and then adding them to a planetary ball mill for ball milling for 1h-8h, for example, 2h-7h, 3h-6h, 4h-5h, etc., to obtain a precursor mixture I, and then evenly placing the obtained precursor mixture I in an open crucible, and then heating it in a muffle furnace at a heating rate of 2°C / min-5°C / min (for example, 2°C / min-3℃ / min, 2℃ / min-3℃ / min, etc.) from room temperature to 900℃-1000℃, for example, 910℃-990℃, 920℃-980℃, 930℃-970℃, 940℃-960℃, 940℃-950℃, and maintain the constant temperature for 10h-20h, for example, 11h-19h, 12h-18h, 13h-17h, 14h-16h, 14h-15h, etc., the atmosphere used is dehumidified and carbon dioxide-removed air, and the sodium ion transition metal oxide is obtained after natural cooling.
[0119] It should be noted that, due to the loss of Na source in the subsequent calcination process, the amount of Na added will be slightly higher than the required Na content in the above-mentioned sodium ion transition metal oxide composition.
[0120] The Na source, Fe source, Mn source, Ni source and Q source in the present application are conventional materials in the art, and those skilled in the art can select them according to actual conditions. For example, the Na source can include Na 2 CO 3 、NaHCO 3 , NaOH and Na 2 O 2 At least one of; the Fe source may include FeO, Fe 2 O 3 and Fe 3 O 4 At least one of; the Mn source may include Mn 2 O 3 , Mn 3 O 4 , MnO and MnO 2 At least one of; the Ni source may include NiO; the Q source may include at least one of an oxide of Q, a salt containing Q, and other compounds.
[0121] It should be noted that if it is necessary to dope the positive electrode active material with the element F, at least one of the Na source, Fe source, Mn source, Ni source and Q source adopts at least one of its corresponding fluorine-containing salts and other compounds, such as sodium fluoride, iron fluoride, manganese fluoride, Ni fluoride and Q fluoride (fluoride salt of Q).
[0122] S200: Mixing and sintering the sodium ion transition metal oxide and the alkaline sodium compound
[0123] In some embodiments of the present application, the above-mentioned sodium ion transition metal oxide and the alkaline sodium compound are mixed according to 0.1≤(b+c) / w≤0.5 (the molar amount of the iron element in the sodium ion transition metal oxide is recorded as b, the molar amount of the nickel element is recorded as c, and the mass proportion of the alkaline sodium compound based on the total amount of the positive electrode active material is w%), and then pre-ground in an agate mortar and added to a planetary ball mill for ball milling for 1h-8h, for example, 2h-7h, 3h-6h, 4h-5h, etc., to obtain a precursor mixture II, and then the obtained precursor The drive mixture II is evenly placed in an open crucible, and then heated from room temperature to 300°C-600°C, such as 350°C-550°C, 400°C-500°C, 450°C-500°C, etc., in a muffle furnace at a heating rate of 2°C / min-5°C / min (e.g., 2°C / min-3°C / min, 2°C / min-3°C / min, etc.), and kept at a constant temperature for 1h-3h, such as 1h-2h, 2h-3h, 1h-1.5h, etc., and the atmosphere used is dehumidified and carbon dioxide-free air. After natural cooling, the positive electrode active material is obtained. The sintering process can make the alkaline sodium compound more evenly distributed on the surface of the sodium ion transition metal oxide and better combined with each other, thereby forming a stable coating layer on the surface of the sodium ion transition metal oxide, improving the structural stability of the positive electrode active material under high voltage, thereby improving the cycle stability and energy density of the battery containing it under high voltage.
[0124] Therefore, the method of the present application can be used to prepare the above-mentioned positive electrode active material with stable structure under high voltage, thereby improving the cycle stability and energy density of the battery containing the positive electrode active material under high voltage.
[0125] The third aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application or the positive electrode active material prepared by the method described in the second aspect.
[0126] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.
[0127] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.
[0128] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bind the positive electrode active material and the binder to the positive electrode current collector. The present application does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0129] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder may include at least one of styrene-butadiene rubber (SBR), water-based acrylic resin, carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA) and polyvinyl alcohol (PVA).
[0130] These materials are all commercially available.
[0131] The fourth aspect of the present application provides a battery, which comprises the positive electrode sheet described in the third aspect of the present application. Thus, the battery has excellent cycle stability and energy density at high voltage.
[0132] A battery is a battery that can be used again by recharging the active materials after discharge.
[0133] It is understandable that the battery proposed in this application is a sodium ion battery.
[0134] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0135] [Negative electrode]
[0136] In a battery, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0137] The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil.
[0138] The specific type of the negative electrode active material is not limited, and active materials known in the art that can be used for the negative electrode of sodium ion batteries can be used, and those skilled in the art can choose according to actual needs. As an example, the negative electrode active material may include but is not limited to at least one of sodium metal, carbon material, alloy material, transition metal oxide and / or sulfide, phosphorus-based material, and titanate material. Specifically, the carbon material may include at least one of hard carbon, soft carbon, amorphous carbon, and nanostructured carbon material; the alloy material may include an alloy material formed by at least one of Si, Ge, Sn, Pb, and Sb; the general formula of the transition metal oxide and sulfide is M x N y , wherein M includes at least one of Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V, and N includes O or S; the phosphorus-based material may include at least one of red phosphorus, white phosphorus, and black phosphorus; the titanate material may include Na 2 Ti 3 O 7 、Na 2 Ti 6 O 13 、Na 4 Ti 5 O 12 , Li 4 Ti 5 O 12 、NaTi 2 (PO 4 ) 3 These materials can be obtained through commercial channels.
[0139] The negative electrode active material layer may also optionally include a binder and a conductive agent. The conductive agent is used to improve the conductivity of the negative electrode active material layer, and the binder is used to firmly bind the negative electrode active material and the binder to the negative electrode current collector. The present application does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0140] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0141] As an example, the binder may include at least one of styrene butadiene rubber (SBR), styrene butadiene rubber (SBCs), water-based acrylic resin, and carboxymethyl cellulose (CMC).
[0142] The negative electrode active material layer may also optionally include a thickener, such as carboxymethyl cellulose (CMC). However, the present application is not limited thereto, and the present application may also use other materials that can be used as thickeners for negative electrode sheets of sodium ion batteries.
[0143] [Electrolyte]
[0144] The electrolyte may include an electrolyte salt and a solvent.
[0145] As an example, the electrolyte sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate, and sodium bis(trifluoromethylsulfonyl)imide.
[0146] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0147] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0148] [Isolation film]
[0149] As the above-mentioned isolation membrane, the present application has no special restrictions and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs. For example, it can include a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0150] The embodiment of the present application has no particular limitation on the shape of the battery, which can be cylindrical, square or any other shape. Figure 2 The secondary battery 1 is a square structure as an example.
[0151] In some embodiments, the battery may include an outer packaging for packaging the positive electrode sheet, the negative electrode sheet, and the electrolyte.
[0152] In some embodiments, the outer package may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.
[0153] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly. The electrode assembly is packaged in the receiving cavity. The number of electrode assemblies contained in the battery can include one or more, which can be adjusted according to demand.
[0154] In some embodiments, the outer packaging of the battery may include a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.
[0155] The outer packaging of the battery may also include a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0156] In some embodiments, the batteries may be assembled into a battery module. The battery module may contain multiple batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0157] Figure 3 2 is an example of a battery module 2. Figure 3 In the battery module 2, the plurality of secondary batteries 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 1 may be fixed by fasteners.
[0158] The battery module 2 may further include a housing having a housing space, in which a plurality of secondary batteries 1 are housed. In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0159] Figure 4 and 5 The battery pack 3 is used as an example. Figure 4 and 5 The battery pack 3 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 4 and a lower box body 5. The upper box body 4 can cover the lower box body 5 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.
[0160] The fifth aspect of the present application provides an electrical device, which includes the battery described in the fourth aspect. Specifically, the battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, and energy storage systems.
[0161] Figure 6 The electrical equipment is used as an example, and the electrical equipment includes a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.
[0162] As another example, the electric device may include a mobile phone, a tablet computer, and a notebook computer. The electric device is usually required to be thin and light, and a battery may be used as a power source.
[0163] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0164] Example 1
[0165] [Preparation of positive electrode active materials].
[0166] Will Na 2 CO 3 , Mn 2 O 3 , Fe 2 O 3 A total of 30 g of sample was weighed according to the molar ratio of Na:Mn:Fe:Ni of 1:0.4:0.3:0.3, and the obtained sample was pre-ground in an agate mortar and added to a planetary ball mill for ball milling for 1 hour to obtain a precursor mixture I. The obtained precursor mixture I was evenly placed in an open crucible, and then heated from room temperature to 950°C in a muffle furnace at a heating rate of 5°C / min, and kept at a constant temperature of 950°C for 15 hours. The atmosphere used was dehumidified and carbon dioxide-free air. After natural cooling, a composition of Na 0.89 Mn 0.4 Fe 0.3 Ni 0.3 O 2The sodium ion transition metal oxide is then mixed with 0.5gNa 2 CO 3 After pre-grinding in an agate mortar, the mixture was added to a planetary ball mill and ball-milled for 1 hour to obtain a precursor mixture II. The obtained precursor mixture II was then evenly placed in an open crucible, and then heated from room temperature to 500°C in a muffle furnace at a heating rate of 5°C / min, and maintained at a constant temperature of 500°C for 2 hours. The atmosphere used was dehumidified and carbon dioxide-free air. After natural cooling, a positive electrode active material with a coating layer on the surface was obtained.
[0167]
Preparation of positive electrode
[0168] The above-obtained positive electrode active material, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in a solvent NMP (N-methylpyrrolidone) at a mass ratio of 80:15:5 to form a uniform positive electrode slurry. The positive electrode slurry was evenly coated on the upper and lower surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, it was punched into a disc with a diameter of 14 mm to obtain a positive electrode sheet.
[0169]
Preparation of negative electrode sheet
[0170] The negative electrode plate is made of metallic sodium.
[0171]
Preparation of electrolyte
[0172] Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed in equal volumes to obtain an organic solvent, followed by NaClO 4 Dissolve in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0173]
Isolation film
[0174] A porous polyethylene film was used as the separator.
[0175]
Preparation of button cell
[0176] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the prepared electrolyte is added to obtain a button battery.
[0177] The button cell containing positive electrode active material of Example 2-30 is the same as Example 1 except for different parameters in the process of preparing the positive electrode active material (see Table 1-6), and the element Q is added in the form of Q oxide, and the F source is added in the form of sodium source NaF.
[0178] The button cell containing the positive electrode active material of Comparative Example 1 is the same as Example 1 except that the process of preparing the positive electrode active material is different.
[0179] The process of preparing the positive electrode active material in Comparative Example 1 comprises: 2 CO 3 , Mn 2 O 3 , Fe 2 O 3 A total of 30 g of sample was weighed according to the molar ratio of Na:Mn:Fe:Ni of 1:0.4:0.3:0.3, and the obtained sample was pre-ground in an agate mortar and added to a planetary ball mill for ball milling for 1 hour to obtain a precursor mixture I. The obtained precursor mixture I was evenly placed in an open crucible, and then heated from room temperature to 950°C in a muffle furnace at a heating rate of 5°C / min, and kept at a constant temperature of 950°C for 15 hours. The atmosphere used was dehumidified and carbon dioxide-free air. After natural cooling, a composition of Na 0.89 Mn 0.4 Fe 0.3 Ni 0.3 O 2 positive electrode active material.
[0180] The button cells containing positive electrode active materials of Comparative Examples 2-3 and 6 are the same as Comparative Example 1 except for the different parameters in the process of preparing the positive electrode active materials (see Tables 1-6), and the element Q is added in the form of Q oxide, and the F source is added in the form of sodium source NaF.
[0181] The button cells containing positive electrode active materials of Comparative Examples 4-5 are the same as those of Example 1 except for different parameters in the process of preparing the positive electrode active materials (see Tables 1-6).
[0182] Considering that sodium will be lost during the sintering process, if you want to obtain a sodium ion transition metal oxide with the subscript x of the Na element being 1, the Na source should be in excess of 0.05-0.2 during the mixing stage. For example, if you want to obtain NaMn 0.4 Fe 0.3 Ni 0.3 O 2 Sodium ion transition metal oxide, then Na 2 CO 3 , Mn 2 O 3 , Fe 2 O 3 , NiO according to the molar ratio of Na:Mn:Fe:Ni is 1.05-1.2:0.4:0.3:0.3. It should be noted that the alkaline sodium compound in Examples 1-30 and Comparative Examples 4-5 is sodium carbonate.
[0183] The compositions of the positive electrode active materials in the batteries of Examples 1-30 and Comparative Examples 1-6 of the present application are shown in Tables 1-6.
[0184]
[0185]
[0186]
[0187]
[0188]
[0189]
[0190]
[0191]
[0192]
[0193]
[0194]
[0195] The surface morphology, BET specific surface area, composition, phase state, space group and interlayer spacing of the sodium ion transition metal oxide, and the proportion of alkaline sodium compounds of the positive electrode active materials in Examples 1-30 and Comparative Examples 1-6 were characterized, and the characterization results are shown in Tables 1-6. The first-cycle discharge specific capacity and the cycle performance of the button batteries of the positive electrode active materials obtained in Examples 1-30 and Comparative Examples 1-6 were characterized, and the characterization results are shown in Table 7.
[0196] Test methods:
[0197] (1) Surface morphology characterization of positive electrode active materials:
[0198] The surface morphology of the positive electrode active material is characterized by using a scanning electron microscope (SEM), for example, a field emission scanning electron microscope (Zeiss Gemini360) is used to characterize the surface morphology of the positive electrode active material according to the JY / T010-1996 standard.
[0199] (2) Characterization of BET specific surface area of positive electrode active materials:
[0200] Using the American Microelectronics multi-station fully automatic specific surface area and pore analyzer GeminiVII2390, about 7g of the sample was placed in a 9cc long tube with a bulb, degassed at 200℃ for 2h, and then placed in the host for testing to obtain the BET specific surface area data of the positive electrode active material 1000.
[0201] (3) Composition characterization of sodium ion transition metal oxides:
[0202] The test is conducted by inductively coupled plasma atomic emission spectrometry: the instrument standard refers to EPA6010D-2014 "Inductively coupled plasma atomic emission spectrometry". The sample is treated by chemical methods to be dissolved into a solution, atomized into a plasma and excited to produce characteristic spectral lines of the elements. The element content is qualitatively and quantitatively analyzed based on the wavelength and intensity of the spectral lines (which are proportional to the concentration).
[0203] Alkaline sodium compound Na in the coating layer of the positive electrode active material 2 CO 3 The content test can be measured by using instruments and methods known in the art, for example, by referring to GB / T 9736-2008 standard. Under an atmosphere free of carbon dioxide, 30 g of the obtained positive electrode active material powder is weighed, 100 ml of pure water is added and stirred for 30 min, and after standing for 10 min, a certain amount of filtrate is removed and titrated with 0.05 mol / L hydrochloric acid standard solution. The instrument used is a Mettler T5 titrator.
[0204] The content of the basic sodium compound NaOH in the coating layer of the positive electrode active material can be measured by using instruments and methods known in the art, for example, by referring to the GB / T 9736-2008 standard. Under an atmosphere free of carbon dioxide and dehumidification, 30 g of the obtained layered oxide powder is weighed, 100 ml of anhydrous ethanol is added and stirred for 30 min, and 10 ml of the filtrate is removed after standing for 10 min and filtered, and then diluted with 50 ml of ultrapure water, and then titrated with a 0.05 mol / L hydrochloric acid standard solution, and the instrument used is a Mettler T5 titrator.
[0205] The sodium content in the composition of the sodium ion transition metal oxide can be obtained by subtracting the total amount of sodium obtained by the above-mentioned inductively coupled plasma emission spectrometry from the alkaline sodium compounds NaOH and Na in the coating layer obtained by the above-mentioned test method. 2 CO 3 The content of other elements in the composition of the sodium ion transition metal oxide can be calculated by the above-mentioned inductively coupled plasma emission spectrometry test, thereby obtaining the composition of the sodium ion transition metal oxide.
[0206] (4) Test of the mass percentage of alkaline sodium compounds in the positive electrode active material: The alkaline sodium compounds NaOH and Na 2 CO 3 The content of is added together to obtain the result.
[0207] (5) Phase state of sodium ion transition metal oxides and interlayer spacing d of 003 crystal plane 003 And space group test:
[0208] In a dry room or glove box, grind the sample to be tested in an agate mortar and pass it through a 350-mesh sieve. Take an appropriate amount of the sieved sample and put it in the middle of the groove of the sample rack so that the loose sample powder is slightly higher than the plane of the sample rack. Take a glass slide and gently press the sample surface to make the sample surface consistent with the frame plane after scraping it flat, and scrape off the excess powder. After the sample is prepared, use the Brucker D8A_A25 X-ray powder diffractometer of BruckerAxS Company in Germany to measure the CuK α The ray is the radiation source, and the wavelength of the ray is The scanning 2θ angle range is 5°-60°, and the scanning rate is 4° / min. After the test is completed, the angle corresponding to the 003 crystal plane is used. According to the Bragg equation 2d·sinθ=λ, and each unit cell of the 003 crystal plane contains three transition metal layers, the interlayer spacing d of the 003 crystal plane can be obtained. 003 By comparing the XRD diffraction peaks of the sample with the standard card of the XRD analysis software, the space group and crystal phase of the sample can be confirmed.
[0209] (6) Initial discharge capacity of positive electrode active materials and battery cycle performance test
[0210] At 25°C, the button cell was charged to 4.2V at a current density of 10mA / g, and then discharged to 1.5V at a current density of 10mA / g. The initial discharge capacity C of the button cell was obtained. 0 Then, the battery was charged and discharged for 50 cycles at a current density of 10 mA / g, and the discharge capacity C of the 50th cycle was taken. 1 . Battery capacity retention rate after 50 cycles = C 1 / C 0 ×100%.
[0211] Figure 7 This is the surface morphology of the positive electrode active material prepared in Example 1. Figure 8 The surface morphology of the positive electrode active material prepared in Comparative Example 1 is shown in FIG. Figure 7-8 It can be seen that the surface of the positive electrode active material of Example 1 has a uniform coating layer, and the surface of the positive electrode active material of Comparative Example 1 is relatively clean without an obvious continuous coating layer. In addition, the surfaces of the positive electrode active materials of Comparative Examples 2-3 and 6 do not have an obvious continuous coating layer. Fig. 9 This is a surface morphology of the positive electrode active material of the button battery of Example 1 after being disassembled after 50 cycles. Fig.10 The surface morphology of the positive electrode active material of the button battery of comparative example 1 after 50 cycles is shown in FIG. Figure 9-10It can be seen that after 50 cycles, the surface of the positive electrode active material of the button battery in Example 1 still has a uniform coating layer and no obvious cracks, while after 50 cycles, obvious cracks appear on the surface of the positive electrode active material of the button battery in Comparative Example 1, which indicates that the positive electrode active material of Example 1 has higher structural stability under high voltage than the positive electrode active material of Comparative Example 1, thereby improving the cycle performance and energy density of the battery in Example 1.
[0212] Table 7
[0213]
[0214]
[0215] Conclusion: It can be seen from the data in Tables 1-6 that sodium carbonate and sodium hydroxide were detected in the positive active materials of Examples 1-31 and Comparative Examples 5-7, and the sodium hydroxide may be obtained from the water absorption reaction of sodium oxide on the surface of the positive active material. Sodium carbonate and sodium hydroxide were also detected in the positive active material of Comparative Examples 1-4. The sodium carbonate came from the sodium source in the mixing process, and the sodium hydroxide may also be obtained from the water absorption reaction of sodium oxide on the surface of the positive active material. It can be seen from the data in Table 7 that Example 1-30 has an excellent capacity retention rate at high voltage compared to the battery of Comparative Examples 1-6, indicating that the positive active material of the present application can improve the cycle stability of the battery. At the same time, the initial discharge specific capacity of the positive active material of Examples 1-30 of the present application is not less than 158 mAh / g, indicating that the battery of the present application has excellent energy density at high voltage. In summary, the positive active material of the present application can simultaneously improve the cycle stability and energy density of the battery at high voltage.
[0216] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A positive electrode active material, characterized in that, it comprises: a core, the core comprising a sodium-ion transition metal oxide containing iron element and / or nickel element, in the sodium-ion transition metal oxide, the molar amount of iron element is denoted as b, the molar amount of nickel element is denoted as c, 0≤b≤0.4, 0≤c≤0.4; a coating layer, the coating layer is provided on at least a part of the surface of the core, the coating layer contains an alkaline sodium compound, based on the total amount of the positive electrode active material, the mass ratio of the alkaline sodium compound is w%, and satisfies: 0.1≤(b + c) / w≤0.
5.
2. The positive electrode active material according to claim 1, characterized in that, 0.2≤(b + c) / w≤0.
4.
3. The positive electrode active material according to claim 1 or 2, characterized in that, the mass ratio w% of the alkaline sodium compound is 0.3wt% - 5wt%, optionally 0.5wt% - 2wt%.
4. The positive electrode active material according to any one of claims 1 - 3, characterized in that, the alkaline sodium compound comprises at least one of sodium hydroxide and sodium carbonate, optionally sodium carbonate.
5. The positive electrode active material according to claim 4, based on the total mass of the coating layer, the mass ratio of sodium carbonate is higher than or equal to 80%.
6. The positive electrode active material according to claim 4 or 5, based on the total mass of the coating layer, the mass ratio of sodium hydroxide is lower than or equal to 10%.
7. The positive electrode active material according to any one of claims 1 - 6, the sodium-ion transition metal oxide comprises: So x Mr a Feb b Ni c Q d O 2-e+δ F e , 0.5≤x≤1.2, 0 < a, 0≤b≤0.4, 0≤c≤0.4, 0≤d, a + b + c + d = 1, 0≤e≤0.2, -0.1≤δ≤0.1, Q comprises at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W and Bi.
8. The positive electrode active material according to any one of claims 1 - 7, characterized in that, the sodium-ion transition metal oxide comprises: So x Mr a Feb b Ni c Q d O 2-e+δ F e , 0.7≤x≤1.2, 0 < a, 0.1≤b≤0.4, 0.1≤c≤0.4, 0≤d≤0.3, a + b + c + d = 1, 0≤e≤0.2, -0.1≤δ≤0.1, Q comprises at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W and Bi, optionally at least one of B, Mg, Al, Si, Ca, Ti, Co, Cu, Zn, Zr, Nb, Mo, La and Bi, based on the total amount of the positive electrode active material, the mass ratio of the alkaline sodium compound is 1wt% - 2wt%.
9. The positive electrode active material according to claim 8, characterized in that, it satisfies at least one of the following conditions: 0.3≤a≤0.6; 0.15≤b≤0.35; 0.15≤c≤0.35; 0.1≤d≤0.2。 10. The positive electrode active material according to claim 8 or 9, characterized in that, 0.5 ≤ (b + c) / a ≤ 2, and optionally 0.5 ≤ (b + c) / a ≤ 1.
5.
11. The positive electrode active material according to any one of claims 8 - 10, characterized in that the phase of the sodium ion transition metal oxide includes the O3 phase, the space group includes R3m, and the layer spacing is 0.53 nm - 0.55 nm.
12. The positive electrode active material according to any one of claims 1 - 7, characterized in that the sodium ion transition metal oxide includes: That x Mn a By c Q d Or 2-e+δ F e , 0.5 ≤ x ≤ 1.2, 0 < a, 0.1 ≤ c ≤ 0.3, 0 ≤ d ≤ 0.3, a + c + d = 1, 0 ≤ e ≤ 0.2, -0.1 ≤ δ ≤ 0.1, Q includes at least one of Li, B, Mg, Al, Si, K, Ca, Ti, Co, Cu, Zn, Ga, Y, Zr, Nb, Mo, In, Sn, Sb, La, Ce, Ta, W, and Bi, and optionally at least one of B, Mg, Al, Si, Ca, Ti, Co, Cu, Zn, Zr, Nb, Mo, La, and Bi, based on the total amount of the positive electrode active material, the mass ratio of the basic sodium compound is 0.5 wt% - 1.5 wt%.
13. The positive electrode active material according to claim 12, characterized in that at least one of the following conditions is satisfied: 0.5≤a≤0.8; 0.15≤c≤0.25; 0.05≤d≤0.15。 14. The positive electrode active material according to claim 12 or 13, characterized in that 0.125 ≤ c / a ≤ 0.45, and optionally 0.2 ≤ c / a ≤ 0.
3.
15. The positive electrode active material according to any one of claims 11 - 14, characterized in that the phase of the sodium ion transition metal oxide includes the P2 phase, the space group includes P63 / mmc, and the layer spacing is 0.55 nm - 0.57 nm.
16. The positive electrode active material according to any one of claims 1 - 15, characterized in that The BET specific surface area of the positive electrode active material is Sm 2 / g, S and w satisfy the relationship: 0.3≤w / S≤3, and 0.5≤w / S≤2 is optional.
17. The positive electrode active material according to any one of claims 1 - 16, characterized in that the positive electrode active material satisfies at least one of the following conditions: The positive electrode active material D v 50 is 2μm-20μm, optional is 4μm-15μm; The BET specific surface area of the positive electrode active material is 0.2 m 2 / g-2m 2 / g, optional 0.3m 2 / g-2m 2 / g; The compaction density of the positive electrode active material at a pressure of 300 MPa is 3.1 g / cm 3 -3.8g / cm 3 , optional 3.2g / cm 3 -3.6g / cm 3 .
18. A method for preparing a positive electrode active material, characterized in that it includes: providing a sodium ion transition metal oxide containing iron element and / or nickel element, in the sodium ion transition metal oxide, the molar amount of iron element is denoted as b, the molar amount of nickel element is denoted as c, 0 ≤ b ≤ 0.4, 0 ≤ c ≤ 0.4; mixing and sintering the sodium ion transition metal oxide and a basic sodium compound to obtain a positive electrode active material, wherein, based on the total amount of the positive electrode active material, the mass ratio of the basic sodium compound is w%, and 0.1 ≤ (b + c) / w ≤ 0.
5.
19. A positive electrode sheet, characterized in that the positive electrode sheet includes the positive electrode active material according to any one of claims 1 - 17 or the positive electrode active material prepared by the method according to claim 18.
20. A battery, characterized in that the battery includes the positive electrode sheet according to claim 19.
21. An electrical device, characterized in that it includes the battery according to claim 20.
Citation Information
Patent Citations
Positive electrode active material, preparation method thereof and sodium ion battery
CN111554919A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN115411258A
Layered positive electrode material of sodium-ion battery and application of layered positive electrode material
CN115528226A
Positive electrode active material and preparation method thereof, sodium ion battery and electric equipment
CN115881917A
Cited By
Positive electrode active material and preparation method thereof, sodium ion battery and electric equipment
CN119361664A
